Madea goes to jail: the play - Perry, Tyler; Lions Gate Home Entertainment (Santa Monica, Calif. : Lions Gate Home Entertainment, 2006)
Madea's about to be sent to the only place she won't be able to talk her way out of ... jail! This tale of everybody's favorite Southern matriarch overflows with all the heartwarming laughter and down-home wisdom synonymous with the name Madea.
Title from container.
Special features: Behind-the-scenes; The making of 'Madea goes to jail'; Bloopers; Trailers.
Tyler Perry, Cerhyl Riley-Grace, Cassi Davis, LaVan Davis, Judy Peterson, Chantell Christopher, Christian Keyes, Ryan Gentles, Brian Hurst, Anndretta Lyle, Crystal Collins, Ron Andrews.
Not rated.
DVD; NTSC, region 1; full screen (1.33:1) presentation; Dolby Digital 2.0 stereo.
English dialogue, English or Spanish subtitles; closed-captioned.
Keywords: Matriarchy -- Georgia -- Atlanta -- Drama; African American women -- Georgia -- Atlanta -- Drama; Police -- Georgia -- Atlanta -- Drama; Anger -- United States -- Drama; Women prisoners -- United States -- Drama; Prostitutes -- United States -- Drama; Public prosecutors -- United States -- Drama; Eccentrics and eccentricities -- United States -- Drama; Families -- United States -- Drama; Feature films; Comedy films; Films for the hearing impaired; Comedy -- Feature; Crime -- Feature; Police -- Feature; Comedy films